ECOLOGICAL CONSCIOUSNESS IN AFRICAN PROSE NARRATIVES FOR CHILDREN (2017)
Ecological consciousness, the awareness created in stories through representation of human interaction with the environment, is paramount in African prose for children. Existing studies have focused mostly on style, didacticism and other contemporary issues, to the neglect of ecological consciousness. This study examined the depiction of ecological consciousness in selected African prose narratives for children with a view to revealing the predominant environmental tropes, ethics and symbols employed in them. Graham Huggan and Helen Tiffin’s postcolonial ecocriticism and Lawrence Buell and Trevor Cairney’s ecocritical criteria were adopted. Eight prose narratives for children were purposively selected from four traditionally-inclined African tales owing to their ecological consciousness (West—Charles Anson-Lawson’s The Greatest Treasure (TGT), East—Verna Aardema’s Bringing the rain to Kapiti plain (BRK), North—George Murphy’s The Enormous Yam (TEY) and Southern Africa—Charles Mungoshi’s Stories from a Shona Childhood (SSC)) and four contemporary African stories (West—Mabel Segun’s The Twins and the Tree Spirits (TTS), East—Donna Jo Napoli and Kadir Nelson’s Mama Miti (MMT), North—Walid Tahir’s Sayeed…Sayeed (SAS), and Southern Africa—Ignatius Musonza’s Ike’s Plant (IKP)). The narratives were subjected to critical textual analysis. The theme of ecological consciousness is depicted through pastoral, georgic and wilderness tropes infused with Traditional Ecological Knowledge (TEK), sustainability, mutuality and subtle domination of nature. Verna Aardema’s BRK, George Murphy’s TEY, Charles Mungoshi’s SSC, Mabel Segun’s TTS and Donna Jo Napoli and Kadir Nelson’s MMT raise awareness through TEK and establish affective relationship that promotes human connectedness with nature. Charles Anson-Lawson’s TGT, Walid Tahir’s SAS and Ignatius Musonza’s IKP underscores sustainability through conservation of water, plants and animals, and prevention of desertification, loss of species, water and air pollution. Mutuality, balance and synergy as significant elements of co-habitation are explicitly recreated in the contemporary stories but are only implied in the traditional tales. The omniscient narrators in SAS, MMT, and TTS serve as agents of change by projecting ecocentric ethical values, which query flagrant domination of nature through apocalyptic tropes of pollution and land degradation, thereby foregrounding the environmental ethics of restrained anthropocentrism and biocentrism. Water and death are dominant symbols signifying life and death in all the narratives. While water symbolises life for both human and non-human nature, natural death is regarded as a form of renewal. Anthropomorphism and romanticisation of nature are employed in the traditional tales to express the symbiotic relationship between human and non-human nature, while the realistic mode is adopted in all the contemporary tales except TTS. To avoid ecophobia while creating ecological consciousness, all the narratives tend towards social ecology. Environmental tropes of sustainability, mutuality and symbols projecting environmental synergism are used to imbue the young audience with ecological consciousness in African prose narratives for children. Eco-critical discourse should be central in the representation of environmental awareness for African children